Correlation of iron deficiency anaemia with glycosylated haemoglobin (HbA1c) levels in non-diabetics: an observational study - Dhapale, Ajay V.; Kamble, Omkar (International Journal of Advances in Medicine, 2021)
Background: Alteration of HbA1c in other conditions such as haemolytic anaemia, pregnancy and haemoglobinopathy has raised questions about its correlation with iron stores. The aim of the study was to correlate iron deficiency anaemia with glycosylated haemoglobin levels among non-diabetics. Methods: The present study was an observational study among non-diabetic patients of iron deficiency anaemia attending our outpatient department. The study was conducted in the department of medicine of a tertiary care hospital in Maharashtra. All the non-diabetic patients more than 18 years with iron deficiency anaemia were included in the present study. Patients with acute coronary syndromes, chronic liver, chronic kidney diseases, malignancies, haemolytic anaemia, pregnancy, HIV positive with known end stage cardiopulmonary disease were excluded from the study. Results: About 86.33% of the patients had mild to moderate anaemia and 10.7% had severe anaemia in the present study. The average values of haemoglobin, serum ferritin, total iron binding capacity, mean corpuscular volume, mean corpuscular haemoglobin, and mean corpuscular haemoglobin concentration and hematocrit significantly improved after the treatment. With treatment of anaemia, glycosylated haemoglobin, fasting blood sugars and post prandial blood sugars also improved significantly when compared to baseline (p<0.001). Conclusions: The average values of haemoglobin, serum ferritin, total iron binding capacity, mean corpuscular volume, mean corpuscular haemoglobin, and mean corpuscular haemoglobin concentration and hematocrit significantly improved after the treatment. With treatment of anaemia, glycosylated haemoglobin, fasting blood sugars and post prandial blood sugars also improved significantly when compared to baseline.